Two cold-sensitive neurons within one sensillum code for different parameters of the thermal environment in the ant Camponotus rufipes - Nagel, Manuel; Kleineidam, Christoph J. (Frontiers in Behavioral Neuroscience, 2015)
Ants show high sensitivity when responding to minute temperature changes and are able to track preferred temperatures with amazing precision. As social insects, they have to detect and cope with thermal fluctuations not only for their individual benefit but also for the developmental benefit of the colony and its brood. In this study we investigate the sensory basis for the fine-tuned, temperature guided behaviors found in ants, specifically what information about their thermal environment they can assess. We describe the dose-response curves of two cold-sensitive neurons, associated with the sensillum coelocapitulum on the antenna of the carpenter ant Camponotus rufipes. One cold-sensitive neuron codes for temperature changes, thus functioning as a thermal flux-detector. Neurons of such type continuously provide the ant with information about temperature transients (TT-neuron). The TT-neurons are able to resolve a relative change of 37% in stimulus intensity (ΔT) and antennal scanning of the thermal environment may aid the ant’s ability to use temperature differences for orientation. The second cold-sensitive neuron in the S. coelocapitulum responds to temperature only within a narrow temperature range. A temperature difference of 1.6°C can be resolved by this neuron type. Since the working range matches the preferred temperature range for brood care of Camponotus rufipes, we hypothesize that this temperature sensor can function as a thermal switch to trigger brood care behavior, based on absolute (steady state) temperature.